From Communist Regime to Liberal Democracy: The Evolution of the Legal System in Lithuania - DEMENKO, Olga Ivanivna; BIELIAUSKAITĖ, Jolanta; ŠLAPKAUSKAS, Vytautas; VAINIUTĖ, Milda (Journal of Advanced Research in Law and Economics; Vol 7 No 5 (2016): Vol 7, No 5(2016): JARLE Volume VII, Issue 5(19), Fall 2016, 2016)
The article analyses the mechanism of the establishment and maintenance of liberal democracy in Lithuania. This is a political and legal process where politicians have to obey the requirements of constitutionalism consciously. The research considers the periodization of the evolution of the legal system in the Republic of Lithuania: from this approach three periods of the development of the relationship between constitutional law and politics are distinguished: (1) the period of priority of politics over constitutional law; (2) the period of the priority of constitutional law over politics and (3) the period of the maintenance of constitutional law as the methodological basis of political-legal thinking in the political life of the state, the period of the maintenance of constitutional law as the methodological basis of political-legal thinking in the political life of the state (since 2004), period coincides with the entry of the Republic of Lithuania to the European Union and the North Atlantic Treaty Organization. The legislation that does not meet the requirements of constitutionalism can be reported not only to the Constitutional Court, but also to the European Court of Human Rights and the European Court of Justice. This period reflects the tendency that the state’s politicians seek to obey the values and norms of the Constitution of the Republic of Lithuania deliberately. It was concluded that the principle of legal continuity is observed regarding the institutional formation of the legal system of Lithuania.
Keywords: legal system; codification; reception; Constitutional Law; Parliament